The Effect of Temperature and pH on the Removal / Recovery of ZN++ from Solution by Chemical Coagulation - Al –Hemiri, Adil; Hameed Al-Taey, Tahseen (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
This work was conducted to study the treatment of industrial waste water, and more particularly those in the General Company of Electrical Industries.This waste water, has zinc ion with maximum concentration in solution of 90 ppm.The reuse of such effluent can be made possible via appropriate treatments, such as chemical coagulation, Na2S is used as coagulant.The parameters that influenced the waste water treatment are: temperature, pH, dose of coagulant and settling time.It was found that the best condition for zinc removal, within the range of operation used ,were a temperature of 20C a pH value of 13 , a coagulant dose of 15 g Na2S /400ml solution and a settling time of 7 days. Under these conditions the zinc concentration was reduced from 90mg/l to 0.003 mg/l.